2015
DOI: 10.1371/journal.pone.0118601
|View full text |Cite
|
Sign up to set email alerts
|

Multi Drug and Other Forms of Drug Resistant Tuberculosis Are Uncommon among Treatment Naïve Tuberculosis Patients in Tanzania

Abstract: BackgroundSurveillance and effective management of drug resistance is important to sustaining tuberculosis (TB) control efforts. We aimed to determine resistance rates to first line anti tuberculosis drugs and to describe factors associated with the resistance to any of the first line anti tuberculosis drugs in Dar es Salaam Tanzania.MaterialsNewly diagnosed, TB patients with neither history of tuberculosis treatment nor isoniazid prophylaxis were included into the study. Sputum specimens were cultured on eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
(35 reference statements)
2
6
0
1
Order By: Relevance
“…These cases received treatment for multi-drug resistance tuberculosis (MDR-TB) as per existing guideline in Tanzania and elsewhere [ 28 , 29 ]. This low proportion of RR-TB best align with findings by Nagu et al who found uncommon cases of MDR-TB among patients without prior exposure to anti-TB drugs in Tanzania [ 30 ]. Despite these strengths, our study has some limitations.…”
Section: Discussionsupporting
confidence: 88%
“…These cases received treatment for multi-drug resistance tuberculosis (MDR-TB) as per existing guideline in Tanzania and elsewhere [ 28 , 29 ]. This low proportion of RR-TB best align with findings by Nagu et al who found uncommon cases of MDR-TB among patients without prior exposure to anti-TB drugs in Tanzania [ 30 ]. Despite these strengths, our study has some limitations.…”
Section: Discussionsupporting
confidence: 88%
“…Like in most sub-Saharan African countries, the HIV epidemic contributes substantially to the high TB incidence in Tanzania, where a-third of the TB patients are co-infected with HIV [2]. Contrarily, drug-resistant TB is still low in this setting [3]. Other risk factors such as poverty also influence the epidemiology of TB in Tanzania [4].…”
Section: Introductionmentioning
confidence: 99%
“…Walaupun dalam beberapa kasus ditemukan resistensi primer namun prevalensi tertinggi penyebaran MDR-TB masih menunjukkan jika penderita yang pernah melakukan pengobatan sebelumnya beresiko tinggi terjadinya MDR-TB. Penderita dengan riwayat pengobatan sebelumnya memiliki kemungkinan resisten 4 kali lebih besar terjadinya resisten dan untuk MDR-TB memiliki 10 kali lebih besar dari pada penderita yang belum pernah mendapatkan pengobatan (Nagu et al, 2015). Panjangnya pengobatan TB menjadikan penderita jenuh untuk menjalankan pengobatannya, kemudian disanalah peran penting pendamping minum obat untuk mengawasi sekaligus mengingatkan dalam pengobatan.…”
Section: Latar Belakangunclassified